2007
DOI: 10.1007/s10071-007-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

How does dominance rank status affect individual and social learning performance in the dog (Canis familiaris)?

Abstract: Dogs can learn effectively to detour around a V-shaped fence after observing a demonstration from either an unfamiliar human or dog demonstrator. We found earlier that there is substantial individual variation between the dogs' performance, even when using the same experimental conditions. Here, we investigate if the subjects' relative dominance rank with other dogs had an effect on their social learning performance. On the basis of the owners' answers to a questionnaire, subjects from multi-dog homes were sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 27 publications
5
72
1
Order By: Relevance
“…In the Two-apparatus condition, the coordination between partners is particularly important; therefore, it is possible that animals closer in rank paid closer attention to one another compared with partners in dyads with larger rank distances. Indeed studies in dogs suggest that subordinates will learn a task from a dominant more readily than vice versa (48), and in rhesus macaques, gaze-following has been observed to be more likely to occur the closer the rank distance between partners (49). Future studies will be needed to test this hypothesis further.…”
Section: Discussionmentioning
confidence: 99%
“…In the Two-apparatus condition, the coordination between partners is particularly important; therefore, it is possible that animals closer in rank paid closer attention to one another compared with partners in dyads with larger rank distances. Indeed studies in dogs suggest that subordinates will learn a task from a dominant more readily than vice versa (48), and in rhesus macaques, gaze-following has been observed to be more likely to occur the closer the rank distance between partners (49). Future studies will be needed to test this hypothesis further.…”
Section: Discussionmentioning
confidence: 99%
“…In chimpanzees for example, subordinate members adjust their food-choice to the visual information of a dominant member, and prefer the food that the dominant member cannot see (Hare et al, 2000). In the case of dogs, Pongrácz et al (2008) found that the perceived dominance status of dogs had an effect on dogs' social learning in a detour task, also depending on the demonstrator species. Subordinate dogs showed significantly better performance after having observed a dog demonstrator in comparison to dominant dogs, which difference could not be Page 10 of 47 A c c e p t e d M a n u s c r i p t detected if the dogs saw a human as the demonstrator.…”
Section: Page 8 Of 47mentioning
confidence: 96%
“…Subordinate dogs showed significantly better performance after having observed a dog demonstrator in comparison to dominant dogs, which difference could not be Page 10 of 47 A c c e p t e d M a n u s c r i p t detected if the dogs saw a human as the demonstrator. We assessed the 'dominance' status of those subjects that lived in a household with other dogs by means of a questionnaire developed by Pongrácz et al (2008) in the aforementioned experiment.…”
Section: Page 8 Of 47mentioning
confidence: 99%
See 2 more Smart Citations